Content of Heavy Metals and Chemical Composition of the Hydraulic Cement Marketed in Costa Rica - Venegas Padilla, Jimmy (2017)
The present study aims to quantify the concentration of heavy metals, specifically lead (Pb), chromium (Cr), and mercury (Hg), and also the chemical composition (CaO, SiO2, Al2O3, Fe2O3 among others) of the hydraulic cement marketed in Costa Rica. The physical parameters of density and fineness confirmed the homogeneity of the samples to determinate accurately the content of the major components and heavy metals in the cements. The mineralogical constitution was determined by X-ray Fluorescence (XRF). Specifically, the cements showed a mass fraction in the range of (61.22 – 63.12) % of CaO, (18.10 – 26.14) % of SiO2, (3.70 – 6.05) % of Al2O3, (2.57 –3.36) % Fe2O3 and (0.60 – 4.09) % de MgO. Other components such as MgO, TiO2, K2O, P2O5,Na2O and Mn2O3 were found on an average mass fraction lower than 1%. Moreover, using the ignition test results and assuming a complete decomposition of the limestone, it was possible to estimate (indirectly) the content of CaCO3 and CaO given by the raw materials. The metal content of the heavy metals was determined using Flame Atomic Absorption Spectroscopy (FAAS), Electrothermal Atomic Absorption Spectroscopy (ETAAS), and Cold Vapor Atomic Absorption Spectroscopy (CVAAS). The analysis demonstrated that the Pb in cements is present in different concentrations ranging the (2.45 ± 0.72) mg kg-1 to the (8.95 ± 1.34) mg kg-1. Chromium (Cr) was presented in higher concentrations of (10.69 ± 0.92) mg kg-1. The Hg concentration was below0.141 ± 0.021 mg kg-1. In general terms, the hydraulic cements marketed and used in Costa Rica have a suitable chemical composition compared with some cements marketed in Germany. The results of the content of heavy metals presented in this study provide significant information for future studies in the area of toxicology, ecotoxicology, standardization and national regulation.